An eye-tracking method to reveal the link between gazing patterns and pragmatic abilities in high functioning autism spectrum disorders - Grynszpan, Ouriel; Nadel, Jacqueline (Frontiers in Human Neuroscience, 2015)
The present study illustrates the potential advantages of an eye-tracking method for exploring the association between visual scanning of faces and inferences of mental states. Participants watched short videos involving social interactions and had to explain what they had seen. The number of cognition verbs (e.g. think, believe, know) in their answers were counted. Given the possible use of peripheral vision that could confound eye-tracking measures, we added a condition using a gaze-contingent viewing window: the entire visual display is blurred, expect for an area that moves with the participant’s gaze. Eleven typical adults and eleven high functioning adults with ASD were recruited. The condition employing the viewing window yielded strong correlations between the average duration of fixations, the ratio of cognition verbs and standard measures of social disabilities.